Pelatihan Peningkatan Kesejahteraan Pelaku UMKM pada Kondisi Pandemi Covid-19 yang Berbasis Syariah di Kelurahan Tanjung Duren Kecamatan Grogol Petamburan Jakarta Barat - R. Ajeng Entaresmen; Nur Aini Chaniago; Detris Sulisto; Sazkia Salsabila (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2021)
The purpose of this activity is to provide training on how to train in order to improve the welfare of MSME actors in the condition of the Sharia-based Covid-19 Pandemic. In times of crisis like the current SMEs must innovate and utilize online marketing and sales channels to maintain business continuity. In the approach to solving the problem of improving the welfare of MSME actors in the sharia-based co-19 pandemic conditions, including: (1). Products Sold According to Consumer Needs; (2). On improving the welfare of MSME actors in the sharia-based co-19 pandemic conditions. (3). Maximize Digital Marketing as a Marketing Strategy, namely: maximize the use of digital marketing, be it using chart applications such as WhatsApp, or social media like Instagram or Facebook; To support digital marketing, improve product photos and content available in digital marketing. (4). Focus on the Health Protocol, namely: Products that are manufactured must comply with safety and health which are the main requirements. For example using gloves, and some of them; The packaging used must also be able to provide confidence from consumers that are not exposed to viruses. In this case, UMKM players open a business of wet cakes and venture into the food and beverage business.